2022
DOI: 10.1111/jfb.15037
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of cold shock and cold stress in fish

Abstract: Temperature is critical in regulating virtually all biological functions in fish. Low temperature stress (cold shock/stress) is an often-overlooked challenge that many fish face as a result of both natural events and anthropogenic activities. In this study, we present an updated review of the cold shock literature based on a comprehensive literature search, following an initial review on the subject by M.R. Donaldson and colleagues, published in a 2008 volume of this journal. We focus on how knowledge on cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 322 publications
(461 reference statements)
0
41
0
Order By: Relevance
“…In summary, even though the role of cold stress in physiology, pathology, and late embryonic development has been broadly addressed (Mollereau, 2015;Reid et al, 2022), the role of cold stress in early embryonic development is largely unknown. Our study newly identified the specific role of mild cold stress in regulating the clustering movement of DFCs and organ LR patterning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, even though the role of cold stress in physiology, pathology, and late embryonic development has been broadly addressed (Mollereau, 2015;Reid et al, 2022), the role of cold stress in early embryonic development is largely unknown. Our study newly identified the specific role of mild cold stress in regulating the clustering movement of DFCs and organ LR patterning.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain a consistent body temperature throughout a range of external environmental temperature changes, endotherms have evolved many conscious behaviors and non-conscious physiological responses such as huddling, increasing activity, constricting blood flow, shivering, and hibernation (Carey et al, 2003;Messmer et al, 2014;Lu et al, 2019). Heterothermic vertebrates such as fish have none of these methods to maintain a consistent temperature, but they have evolved some mechanisms related to cold adaptation/resistance such as the alteration of cell-membrane fluidity (Johnston and Roots, 1964), synthesis of molecular chaperones (Reid et al, 2022), and antifreeze proteins (Cao et al, 2016). By using these mechanisms, fish can live in a range of cold ambient temperatures (Fangue et al, 2014;Chen et al, 2019;Reid et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Zolezzi et al (2011) emphasized the need to study ecological response mechanisms and patterns to thermopeaking. Although scientific research on the thermal behavior of flowing waters gained increased attention within the last decades, research in thermopeaking is still rather scarce (Moreira et al, 2019) especially when it comes to impacts on fish populations (Reid et al, 2022). Here, we fill this knowledge gap by assessing how cold and warm thermopeaking affects juvenile European grayling ( Thymallus thymallus , L.), a key species of Alpine hydropeaking rivers (Hayes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%